2020
DOI: 10.3390/ijerph17093154
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Hemoglobin A1c (HbA1c) and Hyperreflective Dots (HRD) in Diabetic Patients

Abstract: Hyperreflective dots (HRD) are activated retinal microglial cells induced by retinal inflammation in diabetic patients. This study was conducted to compare the HRD count of normal and diabetic subjects; to determine the correlation between hemoglobin A1c (HbA1c) levels and HRD count; to determine HbA1c cut-off levels for the appearance of HRD in diabetic patients. A cross-sectional study was conducted among normal and diabetic patients. Fundus photos, SD-OCT images and HbA1c levels were taken. A total of 25 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Our findings are in accordance with the study by Davoudi et al [23], who reported that mean HbA 1c was significantly higher in patients with HF compared to those without HF (8.5 vs. 7.9, p = 0.03); Wong et al [24] found that there was a linear relationship between HbA 1c levels and HF count with a strong, positive correlation (r = 0.952, n = 83, p< 0.05). Vujosevic et al [16] mentioned the rise in HF in diabetics compared to normal individuals and diabetics without clinical retinopathy.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in accordance with the study by Davoudi et al [23], who reported that mean HbA 1c was significantly higher in patients with HF compared to those without HF (8.5 vs. 7.9, p = 0.03); Wong et al [24] found that there was a linear relationship between HbA 1c levels and HF count with a strong, positive correlation (r = 0.952, n = 83, p< 0.05). Vujosevic et al [16] mentioned the rise in HF in diabetics compared to normal individuals and diabetics without clinical retinopathy.…”
Section: Discussionsupporting
confidence: 93%
“…The limitations of the studies included in this review are: retrospective design of most of these studies; small sample sizes in most; lack of uniformity in HRS evaluation as an outcome (variable macular areas over which HRS was analyzed, manual versus automated counting, variability in the definition of IR, OR and TR and masking of investigators); short duration of follow up; lack of adjustment for confounders like [blood lipid and sugar levels, 45,46 type of macular edema (CME, DRT, SRD)], lack of uniformity in reporting the statistics and outcomes and significant publication bias.…”
Section: Discussionmentioning
confidence: 99%
“…[ 49 ] showed that the presence of HRS was associated with higher total cholesterol and higher low-density lipoprotein levels. Framme et al ,[ 30 ] Wong et al ,[ 50 ] and De Benedetto et al . [ 18 ] have shown that poor glycometabolic control is associated with more HRS.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the studies included in this review include the following: retrospective designs, inadequate sample sizes, varied HRS measurements (i.e., HRS measured in different macular areas, manual versus automated counting, inconsistent definition of retinal layers), short follow-up duration, lack of adjustment for confounders (blood lipid/sugar levels[ 18 30 49 50 ]), and varying statistical reporting methods and significant publication bias. Also, there has been a lack of uniform definition of HRS in these studies.…”
Section: Discussionmentioning
confidence: 99%